Novos casos da doença de chagas em uma área rural do município de Tobias Barreto - Sergipe - Euzébio, Diana Matos (2015)
The human Chagas disease, also called American trypanosomiasis, is considered by the World Health Organization of the 17 most neglected tropical diseases in the world. The eradication of disease vector transmission path in Brazil is not implemented and was confirmed in this study. The objective was to investigate the infection of Chagas disease vector transmission in humans in rural Tobias Barreto. This is a cross-sectional field study with a quantitative approach, which were investigated 255 individuals 0-85 years living in the villages and Alagoinhas Well Clara, selected at random. Participants received information on the risks of the disease, answered a questionnaire on socio-economic and demographic data relevant to the risk of vector transmission in the study area, and gave blood sample after signing the informed consent form. Factors related to transmission of the disease among those surveyed were analyzed using Epi Info version 7.1.4 software. New cases were found, one sororeagente and three inconclusive. The results demonstrate that the vectorial transmission is not interrupted and the disease is not being diagnosed. The wild species of domicialização the region studied assuming the role of Triatoma infestans, may be responsible for maintaining the transmission of the disease, demonstrating the need for changes in policies for prevention and control of disease.